Peningkatan Pelayanan BK di SD Melalui Teknik Empty Chair Bagi Guru SD KKG Gugus Pandanaran UPTD Pendidikan Kecamatan Semarang Tengah - Kusnarto Kurniawan; Awalya Awalya; Eko Nusantoro; Sinta Saraswati; Dian Wahyu Utami; Trubus Inggariani Kencana (Muria Jurnal Layanan Masyarakat, 2019)
This service aims to add new knowledge and skills to elementary school teachers as an effort to optimize guidance and counseling services in elementary schools. Empty chair techniques was one of techniques in counseling that valued can be applied to the teachers even though the education background itself is not counseling education, to solve student’s problem related to communication in social relationship. The methods used in this training were lectures, discussions, simulations, and assignments. The results of this training showed there was improvemwnt empty chair technique mastery from the average pretest of 4,48 to 5,8 for the average post test. The suggestions for the next service is to give assistance to the participants in field practices to make the service more optimal